Microbiological characterization of drinking water and socio-environmental study in the peri-urban area of La Plata, Buenos Aires, Argentina - Falcone, Andrea Celina (2024)
The aim was to analyze the groundwater quality and evaluate the socio-environmental factors associated with the indicators of environmental contamination in the peri-urban area of La Plata. A descriptive cross-sectional study was conducted between 2013 and 2023, and six neighborhoods were selected. Water samples were taken according to the Argentine Food Code and a parasitological analysis of the water was performed using ultrafiltration. Socio-environmental analyses were carried out with semi-structured questionnaires and a generalized linear model was used considering a binomial distribution. Of the total water samples, 70% (75/106) indicated that the water is not suitable for consumption. The highest contamination by total coliforms was observed in Abasto, and the risk of contamination by this indicator was higher (odds ratio.5) compared to other neighborhoods. A moderate percentage of fecal coliforms and Escherichia coli was found in Melchor Romero and El Peligro, although it was higher than that detected in the other neighborhoods. Pseudomonas spp. was observed in all the samples in Arana and in moderate amounts in Abasto and Lisandro Olmos. Entamoeba spp. and Blastocystis spp. were found in a quarter of the water samples. It is essential to manage environmental sanitation and family health access policies.